Chemical evaluation of sesame seeds treated with ionizing radiation and nonionizing radiation - Abdel-Rahim, E. A.; EI-Adawy, Ashga M.; O.M. Abdel-Fatah (2003)
The effect of gamma radiation, microwave radiation, interaction between them; and storage of radiated sesame seeds were investigated to find out the best treatment which lead to the maximum reduction of antinutritional factors (Trypsin inhibitor and Iipoxygenase activities) without significant effect on the chemical constituents. The gamma rays was used at three doses 0 f 2.5, 5.0 and 8.0 K .Gy, microwave radiation was at 70 level power for 2 and 4 min; and the storage of seeds was at room temperature, R.H. 50-55% for six months.
Includes reference.
Summary in Arabic.
1
Keywords: .